Reinvensi Model Pembelajaran Bahasa Arab Dalam Upaya Membendung Segregasi Gender di Sekolah - Afif Amrullah (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2024)
Gender segregation in the educational environment raises a number of complex problems related to equality, educational outcomes and social development. This research focuses on the interaction of gender and language which is rooted in the practice of learning Arabic as a foreign language in schools. The direction this research aims to achieve is the realization of an educational practice, especially Arabic language learning that is more inclusive. In order to achieve this, the author offers a feminist perspective that can be incorporated into the discourse on Arabic language education as a foreign language in Indonesia. This type of research is qualitative descriptive research which aims to collect and analyze existing theories and facts, and then identify problems or examine applicable phenomena and practices. The research model used here is the Research and Development (R&D) model. There are several strategies that could be considered to be implemented, namely: First, the preparation of teaching materials that are inclusive and have more diverse perspectives; Second, avoid depicting individuals in a stereotypical manner. Third, the use of diction in the language of instruction in class is more neutral; Fourth, the need for government support in providing training for teachers; fifth, we hope for active support from the government for school policies and educational institutions that have gender mainstreaming programs.